Health status of patients with self-reported chronic diseases in Jamaica - Boume, Paul A. (Medknow Publications & Media Pvt Ltd, 2009)
BACKGROUND: Developing countries such as Jamaica suffer increasingly from high levels of public health problems related to chronic diseases. AIMS: To examine the physical health status and use a model to determine the significant predictors of poor health status of Jamaicans who reported being diagnosed with a chronic non-communicable disease. METHODS AND MATERIALS: The current study extracted a sub-sample of 714 people from a larger nationally representative cross-sectional survey of 6,783 Jamaicans. A self-administered questionnaire was used to collect the data from the sample. Statistical analysis was performed using chi-square to investigate non-metric variables, and logistic regression to determine predictors of poor health status. RESULTS: Approximately one-quarter 25.3%) of the sample reported that they had poor health status. Thirty-three percent of the sample indicated unspecified chronic diseases: 7.8% arthritis, 28.9% hypertension, 17.2% diabetes mellitus and 13.3% asthma. Asthma affected 47.2% of children and 23.2% of young adults. S ignificant predictors of poor health status of Jamaicans who reported being diagnosed with chronic diseases were: age of respondents, area of residence and inability to work. CONCLUSION: Majority of the respondents in the sample had good health, and adults with poor health status were more likely to report having hypertension followed by diabetes mellitus and arthritis, while asthma was the most prevalent among children. Improvement in chronic disease control and health status can be achieved with improved patient education on the importance of compliance, access to more effective medication and development of support groups among chronic disease patients.